Photoelectric conversion element module and method for producing same

The photoelectric conversion element module achieves high efficiency and durability by using a porous carbon material in the second charge transport layer and electrically connecting it with the transparent conductive film of adjacent elements through conductive adhesive layers and electrodes.

JP7658363B2Active Publication Date: 2025-04-08ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022511778
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-12
Publication Date
2025-04-08
Estimated Expiration
2041-03-12

AI Technical Summary

Technical Problem

Existing photoelectric conversion element modules face challenges in achieving high durability while maintaining high photoelectric conversion efficiency.

Method used

A photoelectric conversion element module is designed with a light-transmitting substrate where each photoelectric conversion element is stacked with a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer made of a porous film containing a carbon material. The second charge transport layer of one photoelectric conversion element is electrically connected to the transparent conductive film of another via a first conductive adhesive layer, a current collecting electrode, and a second conductive adhesive layer.

Benefits of technology

This configuration enhances both the photoelectric conversion efficiency and the durability of the module by stabilizing the electrical connection between photoelectric conversion elements and preventing short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658363000002
    Figure 0007658363000002
  • Figure 0007658363000001
    Figure 0007658363000001
Patent Text Reader

Abstract

This photoelectric conversion element module (1) comprises a plurality of photoelectric conversion elements (15) formed on a light-transmitting substrate (3). Each of the photoelectric conversion elements (15) is obtained by stacking a transparent conductive film (4), a first electric charge transport layer (5), a power generation layer (6), and a second electric charge transport layer (7), in order from the side having the light-transmitting substrate (3). The second electric charge transport layer (7) is formed from a porous film containing a carbon material. Between two adjacent photoelectric conversion elements (15), the second electric charge transport layer (7) of one photoelectric conversion element and the transparent conductive film (4) of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer (9), a current collecting electrode (11), and a second conductive adhesive layer (14).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photoelectric conversion element module and a manufacturing method thereof. [Background technology]

[0002] Solar cells have attracted attention as photoelectric conversion elements that convert light energy into electricity. There are various types of solar cells, such as perovskite solar cells that use a perovskite compound as a power generation layer.

[0003] From the viewpoint of increasing the amount of power that can be obtained, photoelectric conversion element modules are used that are formed by connecting a plurality of photoelectric conversion elements such as the above-mentioned solar cells.

[0004] Here, in the photoelectric conversion element module, it is required to prevent deterioration of characteristics and short circuits between electrodes.

[0005] For example, Patent Document 1 reports that in a solar cell module, when the partitions of adjacent solar cells face each other across a gap, deterioration of characteristics and short circuits between electrodes are less likely to occur. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-152509 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, although there have been reported examples of photoelectric conversion element modules of conventional technology that have high photoelectric conversion efficiency, there is still room for improvement in durability.

[0008] Therefore, an object of the present invention is to provide a photoelectric conversion element module that has high photoelectric conversion efficiency and excellent durability. [Means for solving the problem]

[0009] The present inventors have conducted intensive research in order to solve the above problems. The present inventors have found that a photoelectric conversion element module including a plurality of photoelectric conversion elements each including a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer made of a porous film containing a carbon material, stacked in this order on a light-transmitting substrate, and in which the second charge transport layer of one of two adjacent photoelectric conversion elements and the transparent conductive film of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer, a collector electrode, and a second conductive adhesive layer, has high photoelectric conversion efficiency and excellent durability, and have completed the present invention.

[0010] That is, the present invention aims to advantageously solve the above-mentioned problems, and the photoelectric conversion element module of the present invention is a photoelectric conversion element module comprising a plurality of photoelectric conversion elements formed on a translucent substrate, the photoelectric conversion elements being formed by stacking, in order from the translucent substrate side, a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer, the second charge transport layer being made of a porous film containing a carbon material, and of two adjacent photoelectric conversion elements, the second charge transport layer of one photoelectric conversion element and the transparent conductive film of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer, a collecting electrode, and a second conductive adhesive layer. In this way, a photoelectric conversion element module having a plurality of photoelectric conversion elements each having a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer made of a porous film containing a carbon material stacked in this order on a translucent substrate, and in which the second charge transport layer of one of two adjacent photoelectric conversion elements and the transparent conductive film of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer, a collecting electrode, and a second conductive adhesive layer, has high photoelectric conversion efficiency and excellent durability. In the present invention, the term "porous membrane" refers to a membrane having a plurality of pores formed therein.

[0011] Here, in the photoelectric conversion element module of the present invention, it is preferable that the carbon material contains carbon nanotubes. If the carbon material contains carbon nanotubes, the photoelectric conversion efficiency of the photoelectric conversion element module can be further increased.

[0012] In the photoelectric conversion element module of the present invention, the carbon nanotubes preferably contain single-walled carbon nanotubes, which can provide the second charge transport layer with an excellent function as a hole transport layer and can further increase the photoelectric conversion efficiency of the photoelectric conversion element module.

[0013] In the photoelectric conversion element module of the present invention, it is preferable that the first conductive adhesive layer contains first conductive fine particles, and the first conductive fine particles contain at least one of a carbon material and a metal oxide. If the first conductive adhesive layer contains first conductive fine particles containing at least one of a carbon material and a metal oxide, the durability of the photoelectric conversion element module can be further improved.

[0014] In the photoelectric conversion element module of the present invention, it is preferable that the first conductive adhesive layer contains first conductive fine particles, and at least a part of the first conductive fine particles is embedded in the second charge transport layer. If at least a part of the first conductive fine particles contained in the first conductive adhesive layer is embedded in the second charge transport layer, the photoelectric conversion efficiency of the photoelectric conversion element module can be further increased.

[0015] In the photoelectric conversion element module of the present invention, it is preferable that the first conductive adhesive layer contains first conductive fine particles, the second conductive adhesive layer contains second conductive fine particles, and the average particle diameter of the second conductive fine particles is larger than the average particle diameter of the first conductive fine particles. If the average particle diameter of the second conductive fine particles contained in the second conductive adhesive layer is larger than the average particle diameter of the first conductive fine particles contained in the first conductive adhesive layer, the photoelectric conversion efficiency of the photoelectric conversion element module can be further increased. In the present invention, the "average particle size" of the fine particles can be determined by measuring the particle sizes of 100 randomly selected fine particles using an electron microscope and calculating the average value.

[0016] Furthermore, in the photoelectric conversion element module of the present invention, the power generation layer preferably contains a perovskite compound. If the power generation layer contains a perovskite compound, the photoelectric conversion efficiency of the photoelectric conversion element module can be further increased.

[0017] The present invention aims to advantageously solve the above problems, and the manufacturing method of the photoelectric conversion element module of the present invention is a manufacturing method of a photoelectric conversion element module including a step of connecting two adjacent photoelectric conversion elements among a plurality of photoelectric conversion elements formed on a transparent substrate, wherein the photoelectric conversion element is formed by stacking a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer in this order from the side of the transparent substrate, the second charge transport layer being made of a porous film containing a carbon material, and the second charge transport layer of one of the two adjacent photoelectric conversion elements and the transparent conductive film of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer, a collector electrode, and a second conductive adhesive layer. According to the manufacturing method of the photoelectric conversion element module of the present invention, a photoelectric conversion element module having high photoelectric conversion efficiency and excellent durability can be manufactured. Effect of the Invention

[0018] According to the present invention, it is possible to provide a photoelectric conversion element module having high photoelectric conversion efficiency and excellent durability. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a photoelectric conversion element module according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The photoelectric conversion element module of the present invention is not particularly limited, and may be, for example, a solar cell module such as an organic thin-film solar cell or a perovskite solar cell. Hereinafter, one embodiment of a photoelectric conversion element module of the present invention will be described in detail with reference to FIG.

[0021] (Photoelectric conversion element module) Fig. 1 is a cross-sectional view showing a schematic configuration of a photoelectric conversion element module according to one embodiment of the present invention. The photoelectric conversion element module 1 includes a plurality of photoelectric conversion elements 15 on a light-transmitting substrate 3. As shown in Fig. 1, the photoelectric conversion element module 1 includes two adjacent photoelectric conversion elements 15 on the light-transmitting substrate 3.

[0022] The photoelectric conversion element 15 is formed by laminating a transparent conductive film 4, a first charge transport layer 5, a power generation layer 6, and a second charge transport layer 7 in this order from the light-transmitting substrate 3 side. Here, the second charge transport layer 7 is made of a porous film containing a carbon material. Furthermore, a first conductive adhesive layer 9 is formed on the surface of the second charge transport layer 7 opposite to the side on which the power generation layer 6 is formed. In addition, the surface of the first conductive adhesive layer 9 opposite to the side on which the second charge transport layer 7 is formed is connected to a collector electrode 11. Therefore, the second charge transport layer 7 of the photoelectric conversion element 15 and the collector electrode 11 are electrically connected via the first conductive adhesive layer 9. The collector electrode 11 is formed on a substrate 12. In this specification, a member formed by forming the collector electrode 11 on the substrate 12 may be referred to as a "collecting electrode substrate 10".

[0023] Of two adjacent photoelectric conversion elements 15, the second charge transport layer 7 of one photoelectric conversion element 15 (the left side in Figure 1) and the transparent conductive film 4 of the other photoelectric conversion element 15 (the right side in Figure 1) are electrically connected via the first conductive adhesive layer 9, the collecting electrode 11, and the second conductive adhesive layer 14.

[0024] Here, in FIG. 1, one of the collecting electrodes 11 (left side in FIG. 1) is electrically connected to the second charge transport layer 7 of one of the photoelectric conversion elements 15 via the first conductive adhesive layer 9, as described above. The one of the collecting electrodes 11 extends to the other of the photoelectric conversion elements 15 (right side in FIG. 1). The transparent conductive film 4 of the other of the photoelectric conversion elements 15 extends to the one of the photoelectric conversion elements 15. The second conductive adhesive layer 14 is formed between the part of the one of the collecting electrodes 11 extending to the other of the photoelectric conversion elements 15 and the part of the transparent conductive film 4 of the other of the photoelectric conversion elements 15 extending to the one of the photoelectric conversion elements 15. Therefore, the one of the collecting electrodes 11 and the transparent conductive film 4 of the other of the photoelectric conversion elements 15 are electrically connected to each other via the second conductive adhesive layer 14. As a result, of two adjacent photoelectric conversion elements 15 on the translucent substrate 3, the second charge transport layer 7 of one photoelectric conversion element 15 and the transparent conductive film 4 of the other photoelectric conversion element 15 are electrically connected via the first conductive adhesive layer 9, the collecting electrode 11, and the second conductive adhesive layer 14.

[0025] The first conductive adhesive layer 9 contains first conductive fine particles 8. In FIG. 1, the first conductive fine particles 8 are in contact with both the second charge transport layer 7 and the collecting electrode 11. In the photoelectric conversion element module 1, the first conductive fine particles 8 may be in contact with only one of the second charge transport layer 7 and the collecting electrode 11, or the first conductive fine particles 8 may be in contact with neither the second charge transport layer 7 nor the collecting electrode 11, within a range in which the desired effects of the present invention can be obtained.

[0026] The second conductive adhesive layer 14 includes second conductive fine particles 13. In FIG. 1, the second conductive fine particles 13 are in contact with both the one collector electrode 11 and the transparent conductive film 4 of the other photoelectric conversion element 15. In the photoelectric conversion element module 1, the second conductive fine particles 13 may be in contact with only one of the one collector electrode 11 and the transparent conductive film 4 of the other photoelectric conversion element 15, or the second conductive fine particles 13 may be in contact with neither the one collector electrode 11 nor the transparent conductive film 4 of the other photoelectric conversion element 15, within a range in which the desired effects of the present invention can be obtained. In addition, a plurality of second conductive fine particles 13 may be arranged in a row, and the second conductive fine particles 13 arranged at one end may be in contact with one collector electrode 11, and the second conductive fine particles 13 arranged at the other end may be in contact with the transparent conductive film 4 of the other photoelectric conversion element 15, thereby forming a conductive path from the collector electrode 11 to the transparent conductive film 4.

[0027] In FIG. 1, the transparent conductive film 4 of one photoelectric conversion element 15 and the transparent conductive film 4 of the other photoelectric conversion element 15 are not in contact with each other. In addition, in FIG. 1, one collector electrode 11 and the other collector electrode 11 are not in contact with each other.

[0028] Although partially omitted in Fig. 1, the transparent conductive film 4 of one (left side in Fig. 1) photoelectric conversion element 15 may be electrically connected to the second charge transport layer 7 of the other photoelectric conversion element 15 via the second conductive adhesive layer 14, the collector electrode 11, and the first conductive adhesive layer 9. Similarly, the second charge transport layer 7 of the other (right side in Fig. 1) photoelectric conversion element 15 may be electrically connected to the transparent conductive film 4 of the other photoelectric conversion element 15 via the first conductive adhesive layer 9, the collector electrode 11, and the second conductive adhesive layer 14.

[0029] In the photoelectric conversion element module 1, among the multiple photoelectric conversion elements, in any two adjacent photoelectric conversion elements 15, the second charge transport layer 7 of one photoelectric conversion element 15 and the transparent conductive film 4 of the other photoelectric conversion element 15 may be electrically connected via the first conductive adhesive layer 9, the collector electrode 11, and the second conductive adhesive layer 14. For example, when the photoelectric conversion element module 1 includes three or more photoelectric conversion elements 15, it is sufficient that at least any two of the three or more photoelectric conversion elements 15 are electrically connected by the above-mentioned predetermined method, but from the viewpoint of further increasing the photoelectric conversion efficiency, it is preferable that all of the electrical connections between the photoelectric conversion elements 15 in the photoelectric conversion element module 1 are made by the above-mentioned predetermined method.

[0030] Each of the components constituting the photoelectric conversion element module 1 will be described in order below.

[0031] <Transparent substrate 3> The light-transmitting substrate 3 constitutes a base of the photoelectric conversion element module 1. The light-transmitting substrate 3 is not particularly limited, and examples thereof include a substrate made of glass or synthetic resin, and a film made of synthetic resin.

[0032] The glass constituting the light-transmitting substrate 3 may be, for example, inorganic glass such as soda glass.

[0033] Examples of the synthetic resin constituting the light-transmitting substrate 3 include polyacrylic resin, polycarbonate resin, polyester resin, polyimide resin, polystyrene resin, polyvinyl chloride resin, polyamide resin, polycycloolefin resin, etc. Among them, from the viewpoint of obtaining a thin, light, and flexible photoelectric conversion element module 1, it is preferable to use polyethylene terephthalate (PET) or polyethylene naphthalate (PEN) as the synthetic resin.

[0034] The thickness of the light-transmitting substrate 3 is not particularly limited as long as it can maintain its shape as a substrate. The thickness of the light-transmitting substrate 3 can be, for example, 0.1 mm or more and 10 mm or less.

[0035] <Photoelectric conversion element 15> The photoelectric conversion element module 1 includes a plurality of photoelectric conversion elements 15 formed on a light-transmitting substrate 3. The photoelectric conversion element 15 is formed by laminating, in this order from the light-transmitting substrate 3 side, a transparent conductive film 4, a first charge transport layer 5, a power generation layer 6, and a second charge transport layer 7.

[0036] <<Transparent conductive film 4>> The transparent conductive film 4 is a film made of a metal oxide formed on the surface of the light-transmitting substrate 3. By providing the transparent conductive film 4, it is possible to impart electrical conductivity to the surface of the light-transmitting substrate 3. In this specification, a member formed by forming the transparent conductive film 4 on the surface of the light-transmitting substrate 3 may be referred to as a "transparent conductive substrate 2."

[0037] Examples of the metal oxide constituting the transparent conductive film 4 include fluorine-doped tin oxide (FTO), tin oxide (SnO), indium oxide (In2O3), tin-doped indium oxide (ITO), zinc oxide (ZnO), indium oxide / zinc oxide (IZO), gallium oxide / zinc oxide (GZO), etc. The transparent conductive films of the multiple photoelectric conversion elements 15 in the photoelectric conversion element module 1 shown in FIG. 1 may be made of the same metal oxide or different metal oxides.

[0038] The thickness of the transparent conductive film 4 is not particularly limited as long as it is a thickness that can impart the desired conductivity to the light-transmitting substrate 3, and can be, for example, 1 nm or more and 1 μm or less.

[0039] <<First charge transport layer 5>> The first charge transport layer 5 may be a layer (hole transport layer) composed of a p-type semiconductor, or a layer (electron transport layer) composed of an n-type semiconductor. However, one of the first charge transport layer 5 and the second charge transport layer 7 must be composed of a p-type semiconductor, and the other must be composed of an n-type semiconductor. For example, when the second charge transport layer 7 is composed of a p-type semiconductor, the first charge transport layer 5 is composed of an n-type semiconductor. In the present invention, since the second charge transport layer 7 is made of a porous film containing a carbon material, it is preferable that the first charge transport layer 5 has light transparency whether it is composed of a p-type semiconductor or an n-type semiconductor.

[0040] For example, when the first charge transport layer 5 is an electron transport layer made of an n-type semiconductor, the structure of the first charge transport layer 5 is not particularly limited, and may be a single layer made of an n-type semiconductor, or may be made of two layers, an underlayer and a porous semiconductor layer. Hereinafter, the underlayer and the porous semiconductor layer in the case where the first charge transport layer 5 is made of two layers, that is, the underlayer and the porous semiconductor layer, will each be described in detail.

[0041] <Underlayer> The underlayer is an optional layer. By providing the underlayer, the light-transmitting substrate 3 and the transparent conductive film 4 are prevented from directly contacting the porous semiconductor layer described below. This prevents loss of electromotive force, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved.

[0042] The underlayer may be a porous film or a non-porous dense film, so long as it is made of, for example, an n-type semiconductor, but from the viewpoint of sufficiently preventing the light-transmitting substrate 3 and the transparent conductive film 4 from contacting the porous semiconductor layer, the underlayer is preferably a non-porous dense film. The thickness of the underlayer is not particularly limited, and may be, for example, 1 nm or more and 500 nm or less. The underlayer may also optionally contain an insulating material other than an n-type semiconductor in a proportion that does not impair the properties of the underlayer as an n-type semiconductor.

[0043] <Porous semiconductor layer> The porous semiconductor layer is a porous layer. When the first charge transport layer 5 includes a porous semiconductor layer, the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased.

[0044] The porous semiconductor layer preferably contains a metal oxide and / or an organic compound, more preferably contains fine particles of a metal oxide and / or an organic compound, and even more preferably is formed from fine particles of a metal oxide and / or an organic compound.

[0045] Here, the metal oxide forming the porous semiconductor layer is not particularly limited as long as it functions as an n-type semiconductor, and an example thereof is titanium oxide (TiO2).

[0046] Moreover, examples of organic compounds that form the porous semiconductor layer include fullerene derivatives such as phenyl C61 butyric acid methyl ester (PCBM).

[0047] The average particle size of the metal oxide and / or organic compound particles used in the porous semiconductor layer is preferably 2 nm or more and 80 nm or less, more preferably 30 nm or less. If the average particle size of the particles is small, the resistance of the porous semiconductor layer can be reduced.

[0048] The thickness of the porous semiconductor layer is not particularly limited, but is usually 5 nm or more, preferably 10 nm or more, and usually 500 nm or less, preferably 150 nm or less.

[0049] <<Power Generation Layer 6>> The power generation layer 6 is a layer composed of a material that generates an electromotive force by absorbing light, and from the viewpoint of further increasing the photoelectric conversion efficiency of the photoelectric conversion element module 1, it is preferably a layer containing a perovskite compound, and more preferably a layer made of a perovskite compound (perovskite layer).

[0050] Here, there are no particular limitations on the perovskite compound constituting the power generation layer 6, and any known perovskite compound can be used. Specifically, examples of perovskite compounds that can be used include CH3NH3PbI3, CH3NH3PbBr3, (CH3(CH2)nCHCH3NH3)2PbI4[n=5 to 8], (C6H5C2H4NH3)2PbBr4, and the like.

[0051] The thickness of the power generating layer 6 is not particularly limited, but is preferably 100 nm or more, more preferably 200 nm or more, and is preferably 1 μm or less, more preferably 800 nm or less. By making the thickness of the power generating layer 6 100 nm or more, the electromotive force of the power generating layer 6 can be increased.

[0052] <Joining layer> Although not shown in FIG. 1, the photoelectric conversion element 15 may have a bonding layer at least partially between the power generation layer 6 and the second charge transport layer 7. The bonding layer is made of organic material A and has a composition and properties different from those of the power generation layer 6 and the second charge transport layer 7. Here, a gap may be formed between the power generation layer 6 and the second charge transport layer 8 due to the unevenness of the surface of the power generation layer 6 and the porous film constituting the second charge transport layer 7, but the gap can be filled by providing a bonding layer between the power generation layer 6 and the second charge transport layer 8. Furthermore, by providing the bonding layer in the photoelectric conversion element 15, the transfer of charges between the power generation layer 6 and the second charge transport layer 7 is performed well, so that the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved.

[0053] Examples of the organic material A constituting the bonding layer include polymeric materials exhibiting adhesive properties such as polymethyl methacrylate (PMMA), polymeric materials exhibiting semiconductor properties such as 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene (Spiro-MeOTAD), etc. Also, the bonding layer may be formed by mixing these various materials.

[0054] The thickness of the bonding layer is not particularly limited as long as it can fill the gap formed between the power generation layer 6 and the second charge transport layer 7, and can be appropriately set depending on the surface shapes of the power generation layer 6 and the second charge transport layer 7, etc.

[0055] <<Second charge transport layer 7>> The second charge transport layer 7 may be a layer made of a p-type semiconductor (hole transport layer) or a layer made of an n-type semiconductor (electron transport layer), but one of the first charge transport layer 5 and the second charge transport layer 7 must be made of a p-type semiconductor and the other must be made of an n-type semiconductor. For example, when the above-mentioned first charge transport layer 5 is made of an n-type semiconductor, the second charge transport layer 7 must be made of a p-type semiconductor.

[0056] [Porous film containing carbon material] The second charge transport layer 7 is composed of a porous film containing a carbon material. The method for forming the porous film containing a carbon material may be any method that can form the film at a predetermined position, and the film may be formed by attaching a free-standing film or by a coating method such as printing. However, from the viewpoint of obtaining a desired film thickness and suppressing short circuits, it is preferable that the porous film containing a carbon material is a free-standing film and is attached to form the film.

[0057] Here, when, for example, a metal material is used as the second charge transport layer 7, the metal material contained in the second charge transport layer 7 reacts with a component contained in the perovskite compound, such as iodide ions, contained in the power generation layer 6, and corrosion may occur, resulting in a decrease in durability of the photoelectric conversion element module 1. In addition, when, for example, an organic semiconductor material is used as the second charge transport layer 7, the durability of the photoelectric conversion element module 1 decreases because the organic semiconductor material is insufficient in stability. In contrast, a carbon material does not corrode due to a reaction with the above-mentioned perovskite compound and is also excellent in stability, so that the durability of the photoelectric conversion element module 1 can be increased by using a film containing a carbon material as the second charge transport layer 7.

[0058] Furthermore, by using a porous film as the second charge transport layer 7, it is possible to stabilize the electrical connection between the photoelectric conversion elements 15 and improve the photoelectric conversion efficiency of the photoelectric conversion element module 1. Here, the reason why using a porous film as the second charge transport layer 7 makes it possible to stabilize the electrical connection between the photoelectric conversion elements 15 and improve the photoelectric conversion efficiency of the photoelectric conversion element module 1 is as follows. First, there may be variation in thickness of each layer such as the second charge transport layer 7 constituting the photoelectric conversion element 15. In addition, there may also be variation in particle diameter of the first conductive fine particles 8 contained in the first conductive adhesive layer 9. When a non-porous film is used as the second charge transport layer 7, when the light-transmitting substrate 3 on which the multiple photoelectric conversion elements 15 and the like are formed is bonded to the collecting electrode substrate 10 to manufacture the photoelectric conversion element module 1, the non-porous film is insufficiently flexible and cannot absorb the above-mentioned variations in the layers and the variations in the particle diameter of the conductive fine particles 8. Therefore, some of the first conductive fine particles 8 may not be able to contact the second charge transport layer 7 and / or the collecting electrode 11. In this case, the electrical connection between the photoelectric conversion elements 15 becomes unstable, so that the internal resistance increases and the photoelectric conversion efficiency of the photoelectric conversion element module 1 decreases. In contrast, when a porous film is used as the second charge transport layer 7, when the photoelectric conversion element module 1 is manufactured by bonding the light-transmitting substrate 3 on which the multiple photoelectric conversion elements 15 and the like are formed to the collecting electrode substrate 10, the porous film has excellent flexibility, and can absorb the above-mentioned variations in the layers and the variations in the particle diameter of the conductive fine particles 8 by being deformed or moderately crushed. This can ensure good contact between the first conductive fine particles 8 and the second charge transport layer 7 and the collecting electrode 11. Therefore, the electrical connection between the photoelectric conversion elements 15 can be stabilized, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be improved.

[0059] For the reasons described above, when a porous film containing a carbon material is used as the second charge transport layer 7, a photoelectric conversion element module having high photoelectric conversion efficiency and excellent durability can be obtained.

[0060] Furthermore, when a porous film is used as the second charge transport layer 7, when the light-transmitting substrate 3 on which a plurality of photoelectric conversion elements 15 and the like are formed is bonded to the collecting electrode substrate 10 to manufacture the photoelectric conversion element module 1, the first conductive adhesive layer before curing adjacent to the porous film (second charge transport layer 7) penetrates into the porous film. This makes it possible to prevent the first conductive adhesive layer before curing from expanding due to pressure and reaching other photoelectric conversion elements, thereby preventing short circuits.

[0061] Here, from the viewpoint of further stabilizing the electrical connection and further increasing the photoelectric conversion efficiency of the photoelectric conversion element module 1 by imparting excellent flexibility to the porous film, it is preferable to use a fibrous carbon material as the carbon material contained in the porous film, more preferably to use a fibrous carbon nanostructure, even more preferably to use carbon nanotubes (hereinafter sometimes abbreviated as "CNTs"), and particularly preferably to use single-walled carbon nanotubes. In particular, when a porous film containing single-walled CNTs exhibiting semiconductor properties is used as the carbon material, it is possible to impart the second charge transport layer 7 with the function of an excellent hole transport layer.

[0062] -Single-walled CNT- The single-walled CNTs that can be contained in the porous film preferably have the following properties.

[0063] --(3σ / Av)-- The single-walled CNTs contained in the porous film preferably have a ratio (3σ / Av) of the standard deviation (σ) of the diameters multiplied by 3 (3σ) to the average diameter (Av) of more than 0.20, more preferably more than 0.25, even more preferably more than 0.50, and preferably less than 0.60. If 3σ / Av is more than 0.20 and less than 0.60, even if the amount of single-walled CNTs contained in the porous film is small, the second charge transport layer 7 can be given a sufficient function as a hole transport layer.

[0064] --Average diameter of single-walled CNTs (Av)-- The average diameter (Av) of the single-walled CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, and preferably 15 nm or less, and more preferably 10 nm or less. If the average diameter (Av) of the single-walled CNTs is 0.5 nm or more, aggregation of the single-walled CNTs can be suppressed, and the dispersibility of the single-walled CNTs in the second charge transport layer 7 can be increased. The average diameter (Av) of single-walled CNTs and the ratio (3σ / Av) of the standard deviation (σ) of the diameter multiplied by 3 (3σ) to the average diameter (Av) can be determined by measuring the diameter and length of 100 randomly selected single-walled CNTs using a scanning electron microscope or a transmission electron microscope.

[0065] --t-plot-- The single-walled CNT preferably has a convex t-plot obtained from the adsorption isotherm. The single-walled CNT is more preferably one that has not been subjected to an opening treatment. If the single-walled CNT has a convex t-plot obtained from the adsorption isotherm, the second charge transport layer 7 having excellent strength can be obtained.

[0066] The inflection point of the t-plot of single-walled CNTs is preferably in the range of 0.2≦t(nm)≦1.5, more preferably in the range of 0.45≦t(nm)≦1.5, and even more preferably in the range of 0.55≦t(nm)≦1.0.

[0067] Measurement of the adsorption isotherm of single-walled CNT, creation of t-plots, and analysis of the t-plots can be performed using, for example, a commercially available measuring device, "BELSORP (registered trademark)-mini" (manufactured by BEL JAPAN, Inc.).

[0068] In addition, when the single-walled CNT is evaluated by Raman spectroscopy, it is preferable that the single-walled CNT has a radial breathing mode (RBM) peak. Note that the Raman spectrum of a fibrous carbon nanostructure consisting only of multi-walled carbon nanotubes having three or more walls does not have an RBM. The single-walled CNT preferably has a ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum (G / D ratio) of 0.5 or more and 5.0 or less.

[0069] Single-walled CNTs having the above-mentioned properties can be efficiently produced, for example, by a method in which raw material compounds and a carrier gas are supplied to a substrate having a catalyst layer for CNT production on its surface, and CNTs are synthesized by chemical vapor deposition (CVD), in which the catalytic activity of the catalyst layer is dramatically improved by making a trace amount of an oxidant (catalyst activator) present in the system (super-growth method; see WO 2006 / 011655), and a catalyst layer is formed on the substrate surface by a wet process. Among these, from the viewpoint of easily obtaining a porous film with a large thickness, it is preferable to use, as the single-walled CNTs, single-walled CNTs obtained using the super-growth method (sometimes referred to as "SGCNTs").

[0070] - Carbon material content - The porous film may contain a carbon material such as the above-mentioned single-walled CNT, but is preferably a porous film made of a carbon material. Here, the content of carbon materials such as single-walled CNTs in the porous film is not particularly limited, but is preferably 50 mass % or more, more preferably 75 mass % or more, and even more preferably 90 mass % or more.

[0071] -Other ingredients- The porous membrane may further contain components other than the carbon material within the range in which the desired effects of the present invention can be obtained, such as metal oxide fine particles that are not corrosive to the constituent materials and that aid in electrical conductivity.

[0072] -Film thickness- The thickness of the porous film is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 80 μm or less, when not pressurized in the thickness direction. If the thickness of the porous film is not less than the lower limit when not pressurized in the thickness direction, the above-mentioned variations in each layer and the variations in the particle diameter of the conductive fine particles 8 can be absorbed well, and the electrical connection between the photoelectric conversion elements 15 can be further stabilized, so that the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved. On the other hand, if the thickness of the porous film is not pressurized in the thickness direction and is not more than the upper limit, it is preferable because the second charge transport layer 7 made of the porous film can be easily formed. Note that if the thickness of the porous film is not pressurized in the thickness direction and is not more than the upper limit, the processes such as formation, processing, and installation become complicated and difficult, which is not preferable. The thickness of the porous membrane can be measured by the method described in the Examples of this specification.

[0073] As described above, since the porous film has flexibility, the film thickness decreases when pressure is applied in the thickness direction. For example, the reduction in the thickness of the porous film when it is pressurized in the thickness direction at 0.05 Pa is preferably 1 μm or more, more preferably 2 μm or more, and is preferably less than half the thickness of the porous film before pressurization in the thickness direction. If the reduction in the thickness of the porous film when it is pressurized at 0.05 Pa is equal to or greater than the lower limit, the porous film has excellent flexibility, and can absorb the above-mentioned variations in the layers and the variations in the particle diameter of the conductive fine particles 8, thereby further stabilizing the electrical connection between the photoelectric conversion elements 15 and further improving the photoelectric conversion efficiency of the photoelectric conversion element module 1. On the other hand, if the reduction in the thickness of the porous film when it is pressurized at 0.05 Pa is equal to or less than the upper limit, the self-supporting property of the porous film can be well maintained. The reduction in the thickness of the porous membrane when it is pressurized at 0.05 Pa can be measured by the method described in the Examples of this specification.

[0074] -density- The density of the porous membrane is 0.4 g / cm when no pressure is applied in the thickness direction. 3 It is preferable that the content is 0.6 g / cm or more. 3 It is preferable that the content is 1.5 g / cm or more. 3 It is preferable that the density is 1.2 g / cm or less. 3 It is preferable that the density of the porous film is equal to or less than the lower limit. If the density of the porous film is equal to or less than the upper limit, the porous film can maintain its independence well. On the other hand, if the density of the porous film is equal to or less than the upper limit, the porous film has excellent flexibility, and can absorb the above-mentioned variations in the layers and the variations in the particle diameter of the conductive fine particles 8 well, thereby further stabilizing the electrical connection between the photoelectric conversion elements 15 and further improving the photoelectric conversion efficiency of the photoelectric conversion element module 1. The density of the porous film can be measured by the method described in the Examples of this specification.

[0075] -Method of manufacturing porous membrane containing carbon material- The method for producing a porous film containing a carbon material is not particularly limited, and for example, a method including a step of removing a solvent from a fibrous carbon nanostructure dispersion liquid containing a fibrous carbon nanostructure containing a single-walled CNT as a carbon material, a dispersant, and a solvent to form a porous film (film formation step) can be adopted. Furthermore, the method for producing a porous film containing a carbon material may optionally include a step of dispersing a crude dispersion liquid containing a fibrous carbon nanostructure containing a single-walled CNT, a dispersant, and a solvent to prepare a fibrous carbon nanostructure dispersion liquid (dispersion preparation step) prior to the film formation step.

[0076] --Dispersion liquid preparation process-- In the dispersion preparation step, it is preferable to subject a crude dispersion containing a fibrous carbon nanostructure containing a single-walled CNT, a dispersant, and a solvent to a dispersion treatment that can obtain a cavitation effect or a crushing effect, which will be described later in detail, but is not particularly limited, and to prepare a fibrous carbon nanostructure dispersion by dispersing the fibrous carbon nanostructure containing the single-walled CNT. In this way, by performing a dispersion treatment that can obtain a cavitation effect or a crushing effect, a fibrous carbon nanostructure dispersion in which the fibrous carbon nanostructure containing the single-walled CNT is well dispersed can be obtained. Then, if a porous film is produced using the fibrous carbon nanostructure in which the single-walled CNT is well dispersed, the single-walled CNT can be uniformly dispersed to obtain a porous film having excellent properties such as electrical conductivity, thermal conductivity, and mechanical properties. The fibrous carbon nanostructure dispersion used for producing the porous film may be prepared by dispersing the fibrous carbon nanostructure containing the single-walled CNT in a solvent using a known dispersion treatment other than the above.

[0077] The fibrous carbon nanostructures used in preparing the fibrous carbon nanostructure dispersion may contain at least single-walled CNTs, and may be, for example, a mixture of single-walled CNTs and fibrous carbon nanostructures other than single-walled CNTs (e.g., multi-walled CNTs).

[0078] Here, the content ratio of single-walled CNTs and fibrous carbon nanostructures other than single-walled CNTs in the fibrous carbon nanostructure dispersion can be, for example, 50 / 50 to 75 / 25 in mass ratio (single-walled CNTs / fibrous carbon nanostructures other than single-walled CNTs).

[0079] =Dispersant= The dispersant used in the preparation of the fibrous carbon nanostructure dispersion is not particularly limited as long as it can disperse at least the fibrous carbon nanostructures containing single-walled CNTs and can dissolve in the solvent used in the preparation of the fibrous carbon nanostructure dispersion. For example, a surfactant, a synthetic polymer, or a natural polymer can be used as such a dispersant.

[0080] Examples of the surfactant include sodium dodecylsulfonate, sodium deoxycholate, sodium cholate, and sodium dodecylbenzenesulfonate. Examples of synthetic polymers include polyether diols, polyester diols, polycarbonate diols, polyvinyl alcohol, partially saponified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, acetal group-modified polyvinyl alcohol, butyral group-modified polyvinyl alcohol, silanol group-modified polyvinyl alcohol, ethylene-vinyl alcohol copolymers, ethylene-vinyl alcohol-vinyl acetate copolymer resins, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, acrylic resins, epoxy resins, modified epoxy resins, phenoxy resins, modified phenoxy resins, phenoxy ether resins, phenoxy ester resins, fluorine-based resins, melamine resins, alkyd resins, phenolic resins, polyacrylamides, polyacrylic acids, polystyrene sulfonic acids, polyethylene glycols, and polyvinylpyrrolidone. Further, examples of natural polymers include polysaccharides such as starch, pullulan, dextran, dextrin, guar gum, xanthan gum, amylose, amylopectin, alginic acid, gum arabic, carrageenan, chondroitin sulfate, hyaluronic acid, curdlan, chitin, chitosan, and cellulose, as well as salts or derivatives thereof, where derivatives refer to conventionally known compounds such as esters and ethers.

[0081] These dispersants can be used alone or in combination of two or more. Among them, surfactants are preferred as dispersants because they have excellent dispersibility for fibrous carbon nanostructures including single-walled CNTs, and sodium deoxycholate is more preferred.

[0082] =Solvent= The solvent for the fibrous carbon nanostructure dispersion is not particularly limited, and examples thereof include water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as diethyl ether, dioxane, and tetrahydrofuran, amide polar organic solvents such as N,N-dimethylformamide and N-methylpyrrolidone, and aromatic hydrocarbons such as toluene, xylene, chlorobenzene, orthodichlorobenzene, and paradichlorobenzene. These may be used alone or in combination of two or more.

[0083] In the dispersion liquid preparation step, it is preferable to carry out a dispersion treatment that can obtain, for example, the cavitation effect or the disintegration effect described below.

[0084] = Dispersion processing that produces a cavitation effect = Dispersion treatment that utilizes the cavitation effect is a dispersion method that utilizes shock waves generated by the bursting of vacuum bubbles generated in water when high energy is applied to the liquid. By using this dispersion method, single-walled CNTs can be dispersed well.

[0085] Here, specific examples of dispersion treatments that can obtain a cavitation effect include dispersion treatments using ultrasonic waves, dispersion treatments using a jet mill, and dispersion treatments using high shear stirring. Only one of these dispersion treatments may be performed, or a combination of multiple dispersion treatments may be performed. More specifically, for example, ultrasonic homogenizers, jet mills, and high shear stirring devices are preferably used. These devices may be conventionally known.

[0086] When using an ultrasonic homogenizer to disperse the single-walled CNTs, the crude dispersion liquid may be irradiated with ultrasonic waves by the ultrasonic homogenizer. The irradiation time may be appropriately set depending on the amount of single-walled CNTs, and is preferably 3 minutes or more, more preferably 30 minutes or more, and preferably 5 hours or less, more preferably 2 hours or less. In addition, for example, the output is preferably 20 W or more and 500 W or less, more preferably 100 W or more and 500 W or less, and the temperature is preferably 15 ° C or more and 50 ° C or less.

[0087] Furthermore, when a jet mill is used, the number of treatments may be appropriately set depending on the amount of single-walled CNTs, and is, for example, preferably 2 times or more, more preferably 5 times or more, and preferably 100 times or less, more preferably 50 times or less. Furthermore, for example, the pressure is preferably 20 MPa or more and 250 MPa or less, and the temperature is preferably 15°C or more and 50°C or less.

[0088] Furthermore, when high shear stirring is used, the coarse dispersion liquid is stirred and sheared by a high shear stirring device. The faster the rotation speed, the better. For example, the operating time (the time during which the machine rotates) is preferably 3 minutes to 4 hours, the peripheral speed is preferably 5 m / s to 50 m / s, and the temperature is preferably 15°C to 50°C.

[0089] It is more preferable that the dispersion treatment that produces the above-mentioned cavitation effect is carried out at a temperature of 50° C. or less, because this suppresses concentration changes due to volatilization of the solvent.

[0090] = Dispersion process that produces a disintegrating effect = Dispersion treatments that produce a disintegration effect are not only capable of uniformly dispersing single-walled CNTs in a solvent, but are also more advantageous than dispersion treatments that produce the above-mentioned cavitation effect in that they can suppress damage to single-walled CNTs caused by shock waves when the bubbles disappear.

[0091] In the dispersion process that produces this disintegration effect, shear force is applied to the crude dispersion to disintegrate and disperse the aggregates of fibrous carbon nanostructures containing single-walled CNTs, and then back pressure is applied to the crude dispersion. If necessary, the crude dispersion is cooled, which makes it possible to uniformly disperse the single-walled CNTs in the solvent while suppressing the generation of bubbles. When a back pressure is applied to the crude dispersion, the back pressure applied to the crude dispersion may be reduced to atmospheric pressure in one go, but it is preferable to reduce the pressure in multiple stages.

[0092] --Film forming process-- In the film-forming step, the solvent is removed from the above-mentioned fibrous carbon nanostructure dispersion liquid to form a porous film. Specifically, in the film-forming step, the solvent is removed from the fibrous carbon nanostructure dispersion liquid to form a porous film, for example, by using any one of the following methods (A) and (B). (A) A method in which a dispersion liquid of fibrous carbon nanostructures is applied onto a film-forming substrate, and then the applied dispersion liquid of fibrous carbon nanostructures is dried. (B) A method in which a dispersion of fibrous carbon nanostructures is filtered using a porous film-forming substrate, and the resulting filtrate is dried.

[0093] =Film-forming base material= Here, the film-forming substrate is not particularly limited, and any known substrate can be used. Specifically, examples of the film-forming substrate onto which the fibrous carbon nanostructure dispersion is applied in the above method (A) include resin substrates and glass substrates. Examples of the resin substrates include substrates made of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytetrafluoroethylene (PTFE), polyimide, polyphenylene sulfide, aramid, polypropylene, polyethylene, polylactic acid, polyvinyl chloride, polycarbonate, polymethyl methacrylate, alicyclic acrylic resin, cycloolefin resin, triacetyl cellulose, etc. Examples of the glass substrates include substrates made of ordinary soda glass. In the above method (B), examples of the membrane-forming substrate for filtering the fibrous carbon nanostructure dispersion include filter paper and porous sheets made of cellulose, nitrocellulose, alumina, and the like.

[0094] = Application = In the above method (A), the fibrous carbon nanostructure dispersion liquid can be applied to the film-forming substrate by a known application method, such as dipping, roll coating, gravure coating, knife coating, air knife coating, roll knife coating, die coating, screen printing, spray coating, gravure offset, etc.

[0095] = Filtration = In the above method (B), the fibrous carbon nanostructure dispersion liquid can be filtered using a membrane-forming substrate by a known filtration method, such as natural filtration, reduced pressure filtration, pressure filtration, centrifugal filtration, etc.

[0096] =Drying= A known drying method can be used to dry the fibrous carbon nanostructure dispersion applied to the film-forming substrate in the above method (A) or the filtrate obtained in the above method (B). Examples of the drying method include hot air drying, vacuum drying, hot roll drying, and infrared irradiation. The drying temperature is not particularly limited, but is usually room temperature to 200°C, and the drying time is not particularly limited, but is usually 0.1 to 150 minutes.

[0097] --Post-treatment of porous membrane-- Here, the porous film formed as described above usually contains the components contained in the fibrous carbon nanostructure dispersion, such as single-walled CNTs, fibrous carbon nanostructures other than single-walled CNTs, and dispersants, in the same ratio as in the fibrous carbon nanostructure dispersion. Therefore, in the method for producing a porous film, the porous film formed in the film formation step may be optionally washed to remove the dispersant from the porous film. By removing the dispersant from the porous film, the properties such as the conductivity of the porous film can be further improved.

[0098] The porous membrane can be washed by contacting it with a solvent capable of dissolving the dispersant and dissolving the dispersant in the porous membrane into the solvent. The solvent capable of dissolving the dispersant in the porous membrane is not particularly limited, and the above-mentioned solvents that can be used as the solvent for the fibrous carbon nanostructure dispersion liquid, preferably the same solvent as the solvent for the fibrous carbon nanostructure dispersion liquid, can be used. The contact between the porous membrane and the solvent can be performed by immersing the porous membrane in the solvent or by applying the solvent to the porous membrane. Furthermore, the porous membrane after washing can be dried using a known method.

[0099] In addition, when producing a porous film, the porous film formed in the film formation step may be optionally pressed to further increase the density, and other pore adjustments may be performed as necessary. From the viewpoint of suppressing the deterioration of properties due to damage or destruction of the single-walled CNTs, the pressing pressure during pressing is preferably less than 3 MPa, and it is more preferable not to perform pressing.

[0100] <First conductive adhesive layer 9> The first conductive adhesive layer 9 is a layer that has electrical conductivity and has a function of bonding the second charge transport layer 7 and the current collecting electrode 11 together.

[0101] In the photoelectric conversion element module 1, if there is no first conductive adhesive layer between the second charge transport layer 7 and the collecting electrode 11 and the second charge transport layer 7 and the collecting electrode 11 are directly bonded to each other, the second charge transport layer contains a carbon material as described above and has an uneven surface, resulting in insufficient contact between the second charge transport layer 7 and the collecting electrode 11 and unstable electrical connection, thereby reducing the photoelectric conversion efficiency of the photoelectric conversion element module 1. In contrast, in the photoelectric conversion element module 1, by interposing the first conductive adhesive layer 9 between the second charge transport layer 7 and the collecting electrode 11, the electrical connection between the second charge transport layer 7 and the collecting electrode 11 can be stabilized, thereby improving the photoelectric conversion efficiency of the photoelectric conversion element module 1.

[0102] The first conductive adhesive layer 9 can be formed, for example, by applying a conductive adhesive composition A containing an adhesive material and first conductive fine particles 8 to a predetermined position to form a coating film, and then, if necessary, performing a treatment such as light irradiation, heating, or leaving to stand to harden the adhesive material. The formed first conductive adhesive layer 9 contains a hardened product of the adhesive material and the first conductive fine particles 8.

[0103] The adhesive material is not particularly limited as long as it is a material that can be hardened by some method, and examples of the adhesive material that can be used include photocurable resins such as acrylic resins; thermosetting resins; and two-part mixed reactive adhesives consisting of a base agent and a hardener.

[0104] <<First conductive fine particles 8>> The first conductive fine particles 8 contained in the first conductive adhesive layer 9 are a material that provides electrical connection between the second charge transport layer 7 and the current collecting electrode 11 .

[0105] Here, each particle of the first conductive fine particles 8 is preferably in contact with both the second charge transport layer 7 and the collecting electrode 11. When each particle of the first conductive fine particles 8 is in contact with both the second charge transport layer 7 and the collecting electrode 11, the electrical connection can be further stabilized, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased. In the photoelectric conversion element module 1, there may be first conductive fine particles 8 that are in contact with only one of the second charge transport layer 7 and the collecting electrode 11, or there may be first conductive fine particles 8 that are not in contact with either the second charge transport layer 7 or the collecting electrode 11, within a range in which the desired effects of the present invention can be obtained. Although not shown in FIG. 1, the second charge transport layer 7 is made of a porous film containing a carbon material and has flexibility, so that it is preferable that at least a part of the first conductive fine particles 8 is embedded in the second charge transport layer 7. If at least a part of the first conductive fine particles 8 is embedded in the second charge transport layer 7, the electrical connection can be further stabilized, so that the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved. When at least a part of the first conductive fine particles 8 is embedded in the second charge transport layer 7, a part of the particles of the first conductive fine particles 8 may be present inside the second charge transport layer 7 and the other part may be present outside the second charge transport layer, or the whole particles of the first conductive fine particles 8 may be completely inserted inside the second charge transport layer 7. The state in which at least a part of the first conductive fine particles 8 is embedded in the second charge transport layer 7 can be confirmed by observing the cross section of the photoelectric conversion element module 1 with a scanning electron microscope or the like.

[0106] The first conductive fine particles 8 are not particularly limited, and examples thereof include particles of metals such as Ag, Au, Cu, Al, In, Sn, Bi, Pb, etc., and oxides of these metals; conductive carbon particles such as carbon black; and particles of organic compound particles or inorganic compound particles such as resin particles, the surfaces of which are coated with a conductive material such as metals such as Ag, Au, Cu, etc., or oxides of these metals, for example, particles coated with an Au / Ni alloy. Resin particles coated with a metal may be subject to corrosion as mentioned above, which may result in durability problems. Therefore, from the viewpoint of suppressing corrosion caused by iodide ions of the perovskite compound contained in the power generation layer 6 and further enhancing the durability of the photoelectric conversion element module 1, it is preferable to use particles containing at least one of a carbon material and a metal oxide as the first conductive microparticles 8.

[0107] Here, the average particle diameter of the first conductive fine particles 8 is preferably 20 nm or more, more preferably 30 nm or more, even more preferably 50 nm or more, even more preferably 100 nm or more, even more preferably 120 nm or more, preferably 2000 nm or less, more preferably 1000 nm or less, and even more preferably 500 nm or less. If the average particle diameter of the first conductive fine particles 8 is equal to or greater than the lower limit, the first conductive fine particles 8 can be in good contact with the second charge transport layer 7 and the current collecting electrode 11, so that the electrical connection can be further stabilized, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved. On the other hand, if the average particle diameter of the first conductive fine particles 8 is equal to or less than the upper limit, the second charge transport layer 7 (porous film) can be prevented from being excessively crushed by the first conductive fine particles 8, and the characteristics of the photoelectric conversion element module 1 can be maintained good. The average particle size of the first conductive fine particles 8 is preferably larger than the surface roughness Rz of the second charge transport layer 7 .

[0108] The content of the first conductive fine particles 8 in the first conductive adhesive layer 9 is preferably 6% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. If the content of the first conductive fine particles 8 in the first conductive adhesive layer 9 is equal to or more than the above lower limit, the electrical connection between the second charge transport layer 7 and the collector electrode 11 via the first conductive fine particles is further stabilized, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved. On the other hand, if the content of the first conductive fine particles 8 in the first conductive adhesive layer 9 is equal to or less than the above upper limit, the electrical connection between the second charge transport layer 7 and the collector electrode 11 is well bonded to each other, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further improved.

[0109] <Collecting electrode 11> The current collecting electrode 11 is a conductive film formed on the substrate 12. Providing the current collecting electrode 11 can impart conductivity to the surface of the substrate 12. The conductive film forming the current collecting electrode 11 is not particularly limited as long as it is conductive, such as a metal film or a film made of a metal oxide, but is preferably a film made of a metal oxide from the viewpoint of ease of patterning by laser scribing or the like. As the metal oxide constituting the current collecting electrode 11, the metal oxides mentioned above as the metal oxide constituting the transparent conductive film 4 can be used. The film thickness of current collecting electrode 11 is not particularly limited as long as it is a thickness that can impart a desired electrical conductivity to substrate 12, and can be, for example, 1 nm or more and 1 μm or less.

[0110] <Substrate 12> The substrate 12 is not particularly limited, and examples thereof include a substrate made of glass or synthetic resin, a film made of synthetic resin, etc. As the glass and synthetic resin, the glass and synthetic resin mentioned above as the material constituting the light-transmitting substrate 3 can be used. The thickness of the substrate 12 is not particularly limited as long as it can maintain its shape as a substrate. The thickness of the substrate 12 can be, for example, 0.1 mm or more and 10 mm or less.

[0111] <Second conductive adhesive layer 14> The second conductive adhesive layer 14 has conductivity. The second conductive adhesive layer 14 is formed between two adjacent photoelectric conversion elements 15 on the light-transmitting substrate 3, and bonds a portion of the collector electrode 11 arranged on one (left side in FIG. 1) photoelectric conversion element 15 side that extends to the other (right side in FIG. 1) photoelectric conversion element 15 side and a portion of the transparent conductive film 4 of the other photoelectric conversion element 15 that extends to the one photoelectric conversion element 15 side through the second conductive adhesive layer 14. This allows the two adjacent photoelectric conversion elements 15 on the substrate 3 to be electrically connected while maintaining good transparency of the space between the two adjacent photoelectric conversion elements 15. In addition, when two adjacent photoelectric conversion elements 15 are connected to each other in this manner via the second conductive adhesive layer 14, there is no need to provide a partition made of an insulator between the two adjacent photoelectric conversion elements 15, so the space between the two adjacent photoelectric conversion elements 15 can be narrowed. As a result, the number of photoelectric conversion elements arranged per unit area can be increased, thereby making it possible to highly integrate the photoelectric conversion element module 1.

[0112] The second conductive adhesive layer 14 can be formed, for example, by applying a conductive adhesive composition B containing an adhesive material and second conductive fine particles 13 to a predetermined position to form a coating film, and then, if necessary, performing a treatment such as light irradiation, heating, or leaving to stand to harden the adhesive material. The formed second conductive adhesive layer 14 contains a hardened product of the adhesive material and second conductive fine particles 13.

[0113] The adhesive material is not particularly limited as long as it is a material that can be hardened by some method, and examples of the adhesive that can be used include photocurable resins such as acrylic resins; thermosetting resins; and two-part mixed reactive adhesives consisting of a base agent and a hardener.

[0114] <<Second conductive fine particles 13>> The first conductive fine particles 13 contained in the second conductive adhesive layer 14 are a material that provides electrical connection between the collecting electrode 11 arranged on one side of a photoelectric conversion element 15 and the transparent conductive film 4 of the other photoelectric conversion element 15.

[0115] The second conductive fine particles 13 are preferably in contact with both the collecting electrode 11 arranged on one photoelectric conversion element 15 side and the transparent conductive film 4 of the other photoelectric conversion element 15. By having the second conductive fine particles 13 in contact with both the collecting electrode 11 arranged on one photoelectric conversion element 15 side and the transparent conductive film 4 of the other photoelectric conversion element 15, the electrical connection can be further stabilized, and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased. In the photoelectric conversion element module 1, within a range where the desired effect of the present invention can be obtained, the second conductive fine particles 13 may be in contact with only one of the collector electrodes 11 and the transparent conductive film 4 of the other photoelectric conversion element 15, or the second conductive fine particles 13 may be in contact with neither the collector electrode 11 nor the transparent conductive film 4 of the other photoelectric conversion element 15. Alternatively, a plurality of second conductive fine particles 13 may be arranged in a series, and the second conductive fine particles 13 arranged at one end may be in contact with one collector electrode 11, and the second conductive fine particles 13 arranged at the other end may be in contact with the transparent conductive film 4 of the other photoelectric conversion element 15, thereby forming a conductive path from the collector electrode 11 to the transparent conductive film 4.

[0116] The second conductive fine particles 13 are not particularly limited, and examples thereof include particles of metals such as Ag, Au, Cu, Al, In, Sn, Bi, Pb, etc., and oxides of these metals; conductive carbon particles such as carbon black; and particles of organic compound particles or inorganic compound particles such as resin particles, the surfaces of which are coated with a conductive material such as metals such as Ag, Au, Cu, etc., or oxides of these metals, for example, particles coated with an Au / Ni alloy.

[0117] The second conductive fine particles 13 preferably have a typical shape that is spherical, such as an oblate spheroid or a perfect sphere. Of these, a perfect sphere or an oblate spheroid that is as close to a perfect sphere as possible is preferable. If the second conductive fine particles 13 have a typical shape that is a perfect sphere or an oblate spheroid that is as close to a perfect sphere as possible, the manufacturing efficiency of the photoelectric conversion element module 1 can be improved.

[0118] The maximum dimension R of the second conductive fine particles 13 can be, for example, not less than 10 μm and not more than 30 μm. The maximum dimension R of the second conductive fine particles 13 is a value calculated as the number average value of the major axis lengths obtained by observing 100 particles of the second conductive fine particles 13 under a microscope.

[0119] The average particle diameter of the second conductive fine particles 13 is preferably larger than that of the first conductive fine particles 8. If the average particle diameter of the second conductive fine particles 13 is larger than that of the first conductive fine particles 8, as described above, it becomes easy to bring the first conductive fine particles 8 into contact with both the second charge transport layer 7 and the collecting electrode 11 and the second conductive fine particles 13 into contact with both the collecting electrode 11 and the transparent conductive film 4, so that the electrical connection can be further stabilized and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased.

[0120] In addition, it is preferable that the porous films used in the first charge transport layer 5, the power generation layer 6, and the second charge transport layer 7, the first conductive fine particles 8, and the second conductive fine particles 13 satisfy the relationship represented by the following formula (I). (Thickness of first charge transport layer 5)+(Thickness of power generation layer 6)+(Thickness of porous film used in second charge transport layer 7)+(Average particle diameter of first conductive fine particles 8)>(Average particle diameter of second conductive fine particles 13) (I) In the above formula (I), the "thickness of the porous film used in the second charge transport layer 7" refers to the thickness of the porous film in a state where no pressure is applied in the thickness direction. Furthermore, when the porous film, first conductive fine particles 8, and second conductive fine particles 13 used in the first charge transport layer 5, the power generation layer 6, and the second charge transport layer 7 satisfy the relationship represented by formula (I) above, when the translucent substrate 3 on which a plurality of photoelectric conversion elements 15 and the like are formed is bonded to the collecting electrode substrate 10 to manufacture the photoelectric conversion element module 1, the porous film deforms or is moderately crushed, so that the first conductive fine particles 8 can be brought into contact with both the second charge transport layer 7 and the collecting electrode 11, and the second conductive fine particles 13 can be brought into contact with both the collecting electrode 11 and the transparent conductive film 4. This further stabilizes the electrical connection and further increases the photoelectric conversion efficiency of the photoelectric conversion element module 1.

[0121] In addition, when an auxiliary electrode that can be electrically connected is formed on at least one side in the thickness direction of the second conductive adhesive layer 14, it is preferable that the first charge transport layer 5, the power generation layer 6, the porous film used in the second charge transport layer 7, the first conductive fine particles 8, the second conductive fine particles 13, and the auxiliary electrode satisfy the relationship represented by the following formula (II) instead of the above formula (I). (Thickness of first charge transport layer 5)+(Thickness of power generation layer 6)+(Thickness of porous film used in second charge transport layer 7)+(Average particle diameter of first conductive fine particles 8)>(Average particle diameter of second conductive fine particles 13)+(Thickness of auxiliary electrode) (II) In the above formula (II), the "film thickness of the porous film used in the second charge transport layer 7" refers to the film thickness of the porous film in a state where it is not pressurized in the thickness direction. Also, the "thickness of the auxiliary electrode" in the above formula (II) refers to the total thickness of the auxiliary electrodes. For example, when auxiliary electrodes are formed on both sides of the second conductive adhesive layer 14 in the thickness direction, the "thickness of the auxiliary electrode" in the above formula (II) refers to the total thickness of the auxiliary electrodes formed on both sides of the second conductive adhesive layer 14 in the thickness direction.

[0122] The average particle diameter of the second conductive fine particles 13 is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 80 μm or less. If the average particle diameter of the second conductive fine particles 13 is equal to or greater than the lower limit, the second conductive fine particles 13 can be easily brought into contact with the collector electrode 11 and the transparent conductive film 4, so that the electrical connection can be further stabilized and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased. On the other hand, if the average particle diameter of the second conductive fine particles 13 is equal to or less than the upper limit, the relationship represented by the above formula (I) or (II) can be easily satisfied, so that the electrical connection can be further stabilized and the photoelectric conversion efficiency of the photoelectric conversion element module 1 can be further increased.

[0123] The above-mentioned photoelectric conversion element module 1 has high photoelectric conversion efficiency and excellent durability. The photoelectric conversion element module of the present invention includes a plurality of photoelectric conversion elements each including a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer made of a porous film containing a carbon material, stacked in this order on a light-transmitting substrate, and may further include other members other than the above-mentioned components within a range in which the desired effects of the present invention can be obtained, as long as the second charge transport layer of one photoelectric conversion element and the transparent conductive film of the other photoelectric conversion element are electrically connected to each other through the first conductive adhesive layer, the current collecting electrode, and the second conductive adhesive layer among two adjacent photoelectric conversion elements.

[0124] (Method of manufacturing photoelectric conversion element module) Next, the method for manufacturing the photoelectric conversion element module of the present invention will be described again with reference to Fig. 1. The method for manufacturing the photoelectric conversion element module of the present invention requires a connection step for connecting two adjacent photoelectric conversion elements among a plurality of photoelectric conversion elements formed on a light-transmitting substrate, and optionally includes steps other than the connection step. Hereinafter, as an example of the method for manufacturing the photoelectric conversion element module of the present invention, the method for manufacturing the photoelectric conversion element module 1 will be specifically described.

[0125] <Preparation of Light-Transmitting Substrate 3> In the method for manufacturing the photoelectric conversion element module 1, first, a light-transmitting substrate 3 is prepared. As the light-transmitting substrate 3, those listed in the section "Photoelectric conversion element module" can be used.

[0126] <Formation of Transparent Conductive Film 4> Next, a transparent conductive film 4 is formed on the light-transmitting substrate 3. The method for forming the transparent conductive film 4 is not particularly limited, and known methods such as sputtering and vapor deposition can be used. Note that the formation of the transparent conductive film 4 may be omitted by using a commercially available light-transmitting substrate having a transparent conductive film formed on its surface. Here, a plurality of transparent conductive films 4 are formed in a desired pattern on the light-transmitting substrate 3 so that the photoelectric conversion elements 15 are formed in a desired number and arrangement in the manufactured photoelectric conversion element module 1. For example, a portion of the transparent conductive film can be removed by performing an etching process or the like on the transparent conductive film 4 formed on the entire surface of the light-transmitting substrate 3, thereby obtaining a plurality of transparent conductive films 4 formed in a desired pattern.

[0127] <Formation of First Charge Transport Layer 5> Furthermore, a first charge transport layer 5 is formed on the transparent conductive film 4. The first charge transport layer 5 can be obtained, for example, by forming an underlayer on the transparent conductive film 4 and then forming a porous semiconductor layer.

[0128] [Formation of Underlayer] The method for forming the underlayer is not particularly limited, and for example, the underlayer can be formed by spraying the transparent conductive film 4 with a solution containing a material that forms an n-type semiconductor.

[0129] Here, examples of the method for spraying the solution include a spray pyrolysis method, an aerosol deposition method, an electrostatic spray method, and a cold spray method.

[0130] [Formation of Porous Semiconductor Layer] The method for forming the porous semiconductor layer is not particularly limited. For example, the porous semiconductor layer can be formed by applying a solution containing a precursor of an n-type semiconductor onto the underlayer by spin coating or the like, and drying the solution.

[0131] Here, examples of precursors of n-type semiconductors include titanium alkoxides such as titanium tetrachloride (TiCl4), peroxotitanic acid (PTA), titanium ethoxide, and titanium isopropoxide (TTIP); and metal alkoxides such as zinc alkoxide, alkoxysilane, zirconium alkoxide, and titanium diisopropoxide bis(acetylacetonate).

[0132] The solvent used for the solution containing the n-type semiconductor precursor is not particularly limited, and for example, an alcohol solution such as ethanol can be used.

[0133] Furthermore, the temperature and time for drying the solution applied onto the underlayer are not particularly limited, and may be appropriately adjusted depending on the type of n-type precursor and the type of solvent used.

[0134] <Formation of power generation layer 6> Then, the power generation layer 6 is formed on the first charge transport layer 5. The method of forming the power generation layer 6 includes a vacuum deposition method and a coating method, but is not particularly limited. For example, the power generation layer 6 can be formed by coating a precursor-containing solution containing a precursor of a perovskite compound on the first charge transport layer 5 and baking it. Here, examples of the precursor of the perovskite compound include lead iodide (PbI2) and methylammonium iodide (CH3NH3I). In addition, the solvent contained in the precursor-containing solution is not particularly limited, and examples of the solvent that can be used include N,N-dimethylformamide and dimethylsulfoxide. After coating these solutions, it is also possible to promote the precipitation of the perovskite compound using a poor solvent. In this specification, the term "poor solvent" refers to a solvent in which the perovskite compound does not substantially change during the preparation process. If the perovskite compound does not show any visible changes in appearance, such as turbidity of the film, during the preparation process, it can be said that the perovskite compound does not substantially change.

[0135] Here, the concentration of the precursor of the perovskite compound in the precursor-containing solution may be appropriately selected depending on the solubility of the material that constitutes the perovskite compound, and may be, for example, about 0.5M to 1.5M.

[0136] The method for applying the precursor-containing solution onto the first charge transport layer 5 is not particularly limited, and any known application method such as spin coating, spraying, bar coating, or inkjet printing can be used.

[0137] <Formation of second charge transport layer 7> After the power generation layer 6 is formed, the second charge transport layer 7 is formed on the power generation layer 6. If necessary, the second charge transport layer 7 may be formed on the power generation layer 6 via a bonding layer. For example, the porous membrane is laminated on the power generation layer 6 in a state in which at least one bonding surface of the power generation layer 6 and the porous membrane containing a carbon material retains the solvent X or solution P. This makes it possible to easily manufacture a photoelectric conversion element module 1 having high photoelectric conversion efficiency. As the porous film, the porous film containing the carbon material described above in the section "Photoelectric conversion element module" can be used.

[0138] Examples of the solvent X include poor solvents such as chlorobenzene, toluene, anisole, etc. If these poor solvents are used, for example, when the power generation layer 6 is a perovskite layer made of a perovskite compound, the porous film containing a carbon material can be favorably attached to the power generation layer 6.

[0139] When the second charge transport layer 7 is formed on the power generation layer 6 via a bonding layer, the solution P is used in place of the solvent X. The solution P may be, for example, an organic material-containing solution obtained by dissolving the organic material A constituting the bonding layer in a poor solvent.

[0140] By using a porous membrane impregnated with the above-mentioned solvent X or solution P, the solvent X or solution P can be well retained on at least one of the bonding surfaces of the power generation layer 6 and the porous membrane.

[0141] Here, the porous membrane impregnated with the solvent X or solution P can be obtained, for example, by immersing the porous membrane in the above-mentioned solvent X or solution P and then pulling it out. In this case, the immersion time is not particularly limited and may be appropriately set depending on the type of the solvent or solution used.

[0142] The method for forming the bonding layer is not particularly limited, but from the viewpoint of efficiently manufacturing the photoelectric conversion element module 1, it is preferable to immerse the porous film in an organic material-containing solution obtained by dissolving the organic material A (such as the above-mentioned PMMA) constituting the bonding layer in a poor solvent, and then heat and dry the porous film after pulling it up to form a bonding layer on the porous film, and then attach the porous film to the power generation layer 6 via the bonding layer. In this case, the immersion time, heating temperature, and drying time are not particularly limited, and may be appropriately set depending on the type of organic material-containing solution used. It is preferable to use a poor solvent as the solvent for dissolving the organic material A constituting the bonding layer in order to prevent the influence of residues, but various solvents other than the poor solvent can be used as long as they can be dried to a degree that does not cause any change to the power generation layer 6.

[0143] Furthermore, it is preferable to heat-press the porous film laminated on the power generation layer 6. This allows the formation of a photoelectric conversion element 15 with excellent integrity. At that time, the heating temperature is not particularly limited and can be, for example, about 100°C. The pressure during the heat press is not particularly limited and can be, for example, 0.05 MPa. The pressing time is not particularly limited and can be, for example, 30 seconds. In addition, when the heat press is performed, in order to promote the removal of the solvent contained in the porous film, it is preferable to press in a manner that ensures a volatilization path of the solvent. Specifically, in order to ensure a volatilization path of the solvent, it is preferable to heat press the porous film through a member having voids such as a thick wipe, porous rubber, porous metal, or porous ceramic.

[0144] By the above-mentioned operation, a plurality of photoelectric elements 15 are formed on the light-transmitting substrate. Each photoelectric conversion element 15 is formed by laminating, in this order from the light-transmitting substrate 3 side, a transparent conductive film 4, a first charge transport layer 5, a power generation layer 6, and a second charge transport layer 7, and the second charge transport layer is made of a porous film containing a carbon material.

[0145] <Connection of photoelectric conversion element 15> Among the multiple photoelectric conversion elements 15 formed on the light-transmitting substrate 3, two adjacent photoelectric conversion elements 15 are connected.

[0146] First, the conductive adhesive composition A used to form the above-mentioned first conductive adhesive layer 9 and the conductive adhesive composition B used to form the second conductive adhesive layer 14 are each applied to a predetermined position of a light-transmitting substrate on which a plurality of photoelectric conversion elements are formed. The application of the conductive adhesive composition A and the conductive adhesive composition B may be performed using, for example, a dispenser device.

[0147] Next, the light-transmitting substrate 3 on which the multiple photoelectric conversion elements 15 have been formed and on which the conductive adhesive compositions A and B have been applied at predetermined positions is bonded to the collecting electrode substrate 10 at predetermined positions. The collecting electrode substrate 10 can be produced by forming the collecting electrode 11 on the substrate 12 in the same manner as in the above-mentioned method for forming the transparent conductive film 4 on the light-transmitting substrate 3. The light-transmitting substrate 3 and the collecting electrode substrate 10 may be bonded to each other in a reduced pressure environment using a vacuum bonding device.

[0148] Thereafter, as necessary, light irradiation, heating, standing, or other treatments can be performed to harden the adhesive materials contained in the conductive adhesive compositions A and B, thereby forming a first conductive adhesive layer 9 and a second conductive adhesive layer 14.

[0149] Then, by the above-mentioned operation, a photoelectric conversion element module 1 is obtained, which includes a plurality of photoelectric conversion elements 15 on the light-transmitting substrate 3, and two adjacent photoelectric conversion elements 15 are electrically connected. In the photoelectric conversion element module 1, the second charge transport layer 7 of one of the two adjacent photoelectric conversion elements 15 is connected to the collector electrode 11 via the first conductive adhesive layer 9. The collector electrode 11 extends to the other photoelectric conversion element 15 side. The transparent conductive film 4 of the other photoelectric conversion element 15 extends to the one photoelectric conversion element 15 side. The part of the collector electrode 11 extending to the other photoelectric conversion element 15 side is connected to the part of the transparent conductive film 4 of the other photoelectric conversion element 15 extending to the one photoelectric conversion element 15 side via the second conductive adhesive layer 14. As a result, of two adjacent photoelectric conversion elements 15, the second charge transport layer 7 of one photoelectric conversion element 15 and the transparent conductive film 4 of the other photoelectric conversion element 15 are electrically connected via the first conductive adhesive layer 9, the collecting electrode 11, and the second conductive adhesive layer 14.

[0150] According to the above-mentioned manufacturing method, it is possible to efficiently manufacture the photoelectric conversion element module 1 shown in Fig. 1. Note that the manufacturing method of the photoelectric conversion element module of the present invention is not limited to the above-mentioned method, and may further include steps other than the above-mentioned steps within a range in which the desired effects of the present invention can be obtained. EXAMPLES

[0151] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. Note that the photoelectric conversion element modules manufactured in each of the examples and comparative examples are all modules in which two photoelectric conversion elements are connected in series (i.e., two in series), but the number of series can be selected appropriately depending on the application. In addition, the thickness of the porous membranes produced in the examples and comparative examples and the reduction in thickness when pressure was applied in the thickness direction, as well as the cell performance and performance retention rate of the photoelectric conversion element module were measured using the following methods.

[0152] <Thickness of porous membrane and reduction in thickness when pressure is applied in the thickness direction> The film thickness of the CNT film, which was a porous film containing a carbon material, without being pressed in the thickness direction was measured using a film thickness meter while it was sandwiched between two glass substrates. In addition, at a temperature of 25°C, a CNT film as a porous film containing a carbon material was pressed in the thickness direction at a pressure of 0.05 Pa using a press machine, and the thickness of the CNT film was measured in the same manner as described above. The reduction in thickness when pressed in the thickness direction at 0.05 Pa was calculated from the difference with the thickness when not pressed in the thickness direction.

[0153] <Battery performance> The light source used was a pseudo-sun irradiation device (PEC-L11, manufactured by Peccel Technologies) equipped with an AM1.5G filter and a 150W xenon lamp light source. The light source was 1sun [AM1.5G, 100mW / cm 2 (JIS C8912 Class A). The photoelectric conversion element modules manufactured in each of the examples and comparative examples were connected to a source meter (2400 type source meter, manufactured by Keithley Instruments) and the following current-voltage characteristics were measured. Under 1 sun of light irradiation, the output current was measured while changing the bias voltage in 0.02 V increments from -0.2 V to 2.0 V. The output current was measured by integrating the value from 0.1 s to 0.2 s after changing the voltage at each voltage step. From the above current-voltage characteristic measurement results, the short-circuit current density (mA / cm 2 ), open circuit voltage (V), form factor and photoelectric conversion efficiency (%) were calculated.

[0154] <Performance retention rate> The photoelectric conversion element modules manufactured in each of the examples and comparative examples were used to evaluate the initial battery performance by the above-mentioned method. Next, the photoelectric conversion element modules were placed in a reliability test tank (IH thermohygrostat manufactured by Yamato Scientific Co., Ltd.) kept at a temperature of 45°C and a humidity of 90% RH, and a reliability test was performed in which the modules were left in a light-shielded state without electricity being applied for 1000 hours. Furthermore, the photoelectric conversion element modules after the reliability test were used to evaluate the battery performance by the above-mentioned method. Then, using the conversion efficiency E1 (%) measured in the evaluation of the initial cell performance of the photoelectric conversion element module and the conversion efficiency E2 (%) measured in the evaluation of the cell performance after the reliability test, the performance retention rate (%) was calculated according to the following formula. Performance retention rate (%)=(E2 / E1)×100 A higher performance retention rate indicates that the photoelectric conversion element module has better durability.

[0155] Example 1 <Preparation of a light-transmitting substrate having a transparent conductive film formed thereon> A conductive glass substrate (Sigma-Aldrich, thickness: 2.2 mm) with a fluorine-doped tin (FTO) film (film thickness: 600 nm) formed as a transparent conductive film on the surface of the glass substrate was used, and part of the FTO film was removed by etching. This resulted in a light-transmitting substrate (hereinafter referred to as a "transparent conductive substrate") with a transparent conductive film (FTO film) formed in a pattern of two serial modules.

[0156] <Formation of the first charge transport layer> A solution (Sigma-Aldrich) of titanium diisopropoxide bis(acetylacetonate) dissolved in isopropanol was sprayed onto the surface of the transparent conductive film (FTO film) of the transparent conductive substrate by spray pyrolysis. At this time, a rectangular glass plate was placed to form an underlayer at a predetermined location. As a result, an underlayer made of titanium dioxide (TiO2 dense layer, 30 nm thick) was further formed on the transparent conductive film (FTO film) formed in the pattern of two serial modules, except for the part in contact with the second conductive adhesive layer described below. Next, a solution was prepared by diluting titanium oxide paste (Sigma-Aldrich) with ethanol, and the resulting solution was applied to the surface of the underlayer by spin coating. The solution was then dried on a hot plate at 120°C for 10 minutes. Any coating film that extended beyond the underlayer in a planar view was then wiped off, and the resulting solution was then heat-treated at 450°C for 30 minutes to form a porous semiconductor layer made of titanium dioxide (TiO2) (TiO2 porous layer, thickness 120 nm, average particle diameter of TiO2 microparticles: 20 nm), thereby obtaining a first charge transport layer.

[0157] <Formation of power generation layer> As a solution (1) containing a precursor of the perovskite compound, an N,N-dimethylformamide (DMF) solution containing lead iodide (PbI2) at a concentration of 1.0 M and methylammonium iodide (CH3NH3I) at a concentration of 1.0 M was prepared. The obtained solution (1) was applied to the surface of the first charge transport layer by a spin coating method while dropping chlorobenzene, and then baked at a temperature of 100°C for 10 minutes to form a perovskite layer (thickness 450 nm) as a power generation layer. Thereafter, the perovskite layer protruding from the surface of the first charge transport layer in a planar view was removed to obtain a power generation layer forming substrate having a power generation layer formed in a pattern of two serial modules.

[0158] <Preparation of porous film containing carbon material (CNT film)> A porous film containing single-walled CNTs as a carbon material (CNT film) was produced according to the following procedure. 1.0 g of carbon nanotubes (manufactured by Zeon Corporation, product name "ZEONANO SG101", single-walled CNT (SGCNT), average diameter (Av): 3.5 nm, G / D ratio: 2.1, t-plot is upwardly convex with unopened treatment) was added to 500 mL of 2 mass% aqueous solution of sodium deoxycholate (DOC) as a solvent containing a dispersant, to obtain a crude dispersion containing DOC as a dispersant. This crude dispersion was filled in a high-pressure homogenizer (manufactured by Biryu Co., Ltd., product name "BERYU SYSTEM PRO") having a multistage pressure control device (multistage pressure reducer) that applies back pressure during dispersion, and the crude dispersion was dispersed at a pressure of 100 MPa. Specifically, a shear force was applied to the crude dispersion while applying back pressure to disperse the fibrous carbon nanostructures containing single-walled CNT, and a fibrous carbon nanostructure dispersion containing single-walled CNT was obtained. The dispersion treatment was carried out for 10 minutes while the dispersion liquid flowing out of the high-pressure homogenizer was returned to the high-pressure homogenizer. 50 g of the prepared fibrous carbon nanostructure dispersion containing single-walled CNT was added to a 200 mL beaker, and 50 g of distilled water was added to dilute it twice, and filtration was performed under a condition of 0.09 MPa using a vacuum filtration device equipped with a membrane filter. After filtration, the CNT film formed on the membrane filter was washed by passing isopropyl alcohol and water through the vacuum filtration device, and then air was passed through for 15 minutes. Next, the prepared CNT film / membrane filter was immersed in ethanol, and the CNT film was peeled off from the membrane filter to obtain a CNT film (A) as a porous film containing a carbon material. The obtained CNT film (A) was the same size as the membrane filter, had excellent film-forming properties, and maintained its film state even after being peeled off from the filter, exhibiting excellent self-supporting properties. The film density of the obtained CNT film (A) was measured based on the volume and weight calculated from the film thickness using a contact step gauge, and the density was 0.85 g / cm. 3 Furthermore, when measured according to the above-mentioned method, the CNT film (A) as a porous film containing a carbon material had a thickness of 20 μm when not pressurized in the thickness direction, and the reduction in thickness when pressurized in the thickness direction at 0.05 Pa was 2 μm.

[0159] <Formation of second charge transport layer> The CNT film (A) cut to a predetermined size was immersed in chlorobenzene for 10 seconds, and then the CNT film (A) was pulled up from the chlorobenzene to obtain a CNT film (1) impregnated with chlorobenzene. The CNT film (1) was then laminated on the above-mentioned power generation layer formation substrate heated on a hot plate at a temperature of 100°C, and the resulting laminate was pressed (heated press) from the CNT film (1) side in the thickness direction at a pressure of 0.05 Pa to form a second charge transport layer. This resulted in the formation of two adjacent photoelectric conversion elements on the light-transmitting substrate.

[0160] <Production of photoelectric conversion element modules> Carbon black (average particle diameter: 120 nm) as the first conductive fine particles was added to "TB3035B" (manufactured by ThreeBond Co., Ltd.) as the acrylic resin adhesive material so as to be 10 mass %, and the mixture was mixed uniformly using a centrifugal mixer to prepare conductive adhesive composition A to be used for forming the first conductive adhesive layer. Next, "Micropearl AU" manufactured by Sekisui Chemical Co., Ltd. (conductive microparticles with gold-plated surfaces, typical shape: spherical, maximum dimension: 20 μm, average particle diameter: 20 μm) was added as the second conductive microparticles to "TB3035B" (manufactured by ThreeBond Co., Ltd.), an acrylic resin used as the adhesive material, so as to reach 13.5 mass%, and the mixture was mixed uniformly using a centrifugal mixer to prepare conductive adhesive composition B used to form the second conductive adhesive layer. In addition, a current collecting electrode substrate was prepared in the same manner as in the preparation of the transparent conductive substrate described above, in which current collecting electrodes were formed on a substrate in a module pattern connected in series with two electrodes. Then, a dispenser was used to apply the conductive adhesive composition A and the conductive adhesive composition B to the predetermined positions of the light-transmitting substrate on which the photoelectric conversion element was formed, and a vacuum lamination device was used to bond the collector electrode substrate to the predetermined positions under reduced pressure. After that, light was irradiated from a metal halide lamp to form a first conductive adhesive layer containing the first conductive fine particles and a second conductive adhesive layer containing the second conductive fine particles. This resulted in a photoelectric conversion element module in which two adjacent photoelectric conversion elements were connected in series. In the obtained photoelectric conversion element module, the second charge transport layer of one of the two adjacent photoelectric conversion elements is connected to the collector electrode via the first conductive adhesive layer. The part of the collector electrode extending toward the other photoelectric conversion element is connected to the part of the transparent conductive film of the other photoelectric conversion element extending toward one photoelectric conversion element 15 via the second conductive adhesive layer. Therefore, the second charge transport layer of one photoelectric conversion element and the transparent conductive film of the other photoelectric conversion element are electrically connected via the first conductive adhesive layer, the collector electrode, and the second conductive adhesive layer. The obtained photoelectric conversion element module was used to measure the cell performance and performance retention rate. The results are shown in Table 1. When a cross section of the obtained photoelectric conversion element module was observed with a scanning electron microscope, it was confirmed that at least a part of the first conductive fine particles 8 was embedded in the second charge transport layer 7 .

[0161] Example 2 A photoelectric conversion element module was manufactured in the same manner as in Example 1, except that in the manufacture of the photoelectric conversion element module of Example 1, tin-doped indium oxide (ITO) fine particles (average particle diameter: 30 nm) were used as the first conductive fine particles instead of carbon black (average particle diameter: 120 nm). Measurements were performed using the obtained photoelectric conversion element module in the same manner as in Example 1. The results are shown in Table 1.

[0162] Example 3 In the manufacture of the photoelectric conversion element module of Example 1, a photoelectric conversion element module was manufactured in the same manner as in Example 1, except that a Ti layer was formed as an auxiliary electrode by a sputtering method using a mask in the portion where the second conductive adhesive layer was to be formed. Measurements were performed in the same manner as in Example 1 using the obtained photoelectric conversion element module. The results are shown in Table 1.

[0163] Comparative Example 1 In the manufacture of the photoelectric conversion element module of Example 1, the photoelectric conversion element module was manufactured in the same manner as in Example 1, except that the conductive adhesive composition A was not applied to a predetermined position of the translucent substrate on which the photoelectric conversion element was formed. As a result, in the photoelectric conversion element in the obtained photoelectric conversion element module, the first conductive adhesive layer was not present, and the second charge transport layer and the collecting electrode were directly bonded to each other. Using the obtained photoelectric conversion element module, measurements were performed in the same manner as in Example 1. The results are shown in Table 1.

[0164] Comparative Example 2 In the formation of the second charge transport layer of Example 1, instead of the CNT film (A) which is a porous film containing a carbon material, a composite material film (film thickness: 150 nm) prepared by the following method was used, and in the manufacture of the photoelectric conversion element module of Example 1, instead of carbon black (average particle diameter: 120 nm), Sekisui Chemical's "Micropearl AU" (conductive fine particles with gold plating on the surface, representative shape: spherical, maximum dimension: 3 μm, average particle diameter: 3 μm) was used as the first conductive fine particles, and the average particle diameter (maximum dimension) of Sekisui Chemical's "Micropearl AU" (conductive fine particles with gold plating on the surface, representative shape: spherical) used as the second conductive fine particles was changed from 20 μm to 4 μm. Except for this, a photoelectric conversion element module was manufactured in the same manner as in Example 1. Measurements were performed in the same manner as in Example 1 using the obtained photoelectric conversion element module. The results are shown in Table 1. <Preparation of composite membrane> A composite membrane was formed by forming a Spiro-MOTAD layer and an Au layer using the method described in a non-patent document (Energy Environ. Sci., 2018, 11, 952-959).

[0165] [Table 1]

[0166] In Table 1, "FTO" stands for fluorine-doped tin oxide; "ITO" refers to tin-doped indium oxide; "MAPbI3" refers to CH3NH3PbI3.

[0167] From Table 1, it can be seen that the photoelectric conversion element modules of Examples 1 to 3, which include a plurality of photoelectric conversion elements each having a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer made of a porous film containing a carbon material stacked in this order on a translucent substrate, and in which the second charge transport layer of one of two adjacent photoelectric conversion elements and the transparent conductive film of the other photoelectric conversion element are electrically connected via a first conductive adhesive layer, a collecting electrode, and a second conductive adhesive layer, have high photoelectric conversion efficiency and excellent durability. On the other hand, it is clear that the photoelectric conversion element module of Comparative Example 1, which does not use the first conductive adhesive layer, is inferior in photoelectric conversion efficiency. Moreover, it is understood that the photoelectric conversion element module of Comparative Example 2, in which a material other than the porous film containing a carbon material was used as the second charge transport layer, was inferior in durability. [Industrial Applicability]

[0168] According to the present invention, it is possible to provide a photoelectric conversion element module having high photoelectric conversion efficiency and excellent durability. [Explanation of symbols]

[0169] 1. Photoelectric conversion element module 2 Transparent conductive substrate 3 Translucent substrate 4. Transparent conductive film 5 First charge transport layer 6 Power Generation Layer 7 Second charge transport layer 8 First conductive fine particles 9 First conductive adhesive layer 10 Collecting electrode substrate 11 Current collecting electrode 12 Substrate 13 Second conductive fine particles 14 Second conductive adhesive layer 15 Photoelectric conversion element

Claims

1. A photoelectric conversion element module including a plurality of photoelectric conversion elements formed on a light-transmitting substrate, the photoelectric conversion element is formed by laminating, in this order from the light-transmitting substrate, a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer, the second charge transport layer is made of a porous film containing a carbon material, the second charge transport layer of one of the two adjacent photoelectric conversion elements is electrically connected to the transparent conductive film of the other photoelectric conversion element via a first conductive adhesive layer, a collecting electrode, and a second conductive adhesive layer; the first conductive adhesive layer includes first conductive particles, and at least a portion of the first conductive particles are embedded in the second charge transport layer; Photoelectric conversion element module.

2. The photoelectric conversion element module according to claim 1 , wherein the carbon material includes carbon nanotubes.

3. The photoelectric conversion element module according to claim 2 , wherein the carbon nanotubes contain single-walled carbon nanotubes.

4. the first conductive adhesive layer includes first conductive fine particles, 4. The photoelectric conversion element module according to claim 1, wherein the first conductive fine particles contain at least one of a carbon material and a metal oxide.

5. the first conductive adhesive layer includes first conductive fine particles, the second conductive adhesive layer includes second conductive particles; 5. The photoelectric conversion element module according to claim 1, wherein an average particle size of the second conductive fine particles is larger than an average particle size of the first conductive fine particles.

6. The photoelectric conversion element module according to any one of claims 1 to 5, wherein the power generation layer contains a perovskite compound.

7. A method for manufacturing a photoelectric conversion element module, comprising a step of connecting two adjacent photoelectric conversion elements among a plurality of photoelectric conversion elements formed on a light-transmitting substrate, the method comprising the steps of: the photoelectric conversion element is formed by laminating, in this order from the light-transmitting substrate, a transparent conductive film, a first charge transport layer, a power generation layer, and a second charge transport layer, the second charge transport layer is made of a porous film containing a carbon material, the second charge transport layer of one of the two adjacent photoelectric conversion elements is electrically connected to the transparent conductive film of the other photoelectric conversion element via a first conductive adhesive layer, a collecting electrode, and a second conductive adhesive layer; The first conductive adhesive layer includes first conductive fine particles, and at least a portion of the first conductive fine particles are embedded in the second charge transport layer.

Citation Information

Patent Citations

  • Solar cell module and method of manufacturing the same

    JP2017152509A

  • Opto-electronic device module and method for manufacturing the same

    US20160196927A1

  • Multilayer carbon nanotube film-containing devices

    US20180330891A1

  • Multi-junction photoelectric converter, integrated multi-junction photoelectric converter, and method for manufacturing same

    WO2011024534A1